Study Patterns Of Assistance Field School Integrated Crop Management Rice In Riau Province - Anis Fahri; Dorlan Sipahutar; Amiruddin Saleh (Institut Pertanian Bogor, 2012)
ABSTRACT Study pattern of Assistance Field School Integrated Crop Management (FS-ICM) Rice in Riau Province was conducted in 2011 focused on acquiring data and information (FS-ICM) attending patterns were effective. Experiment was conducting in nine county region of Riau Province. Stipulating location sample of data mining and farming groups in purposive random sampling method. Primary data collected through focus group discussions (FGD), involved an extension worker, community leaders and participating farmers (FS-ICM) as well as ICM demonstration plot farmer cooperators. Collected data had been validated, and classified regarding clustered topic in order information distributed related to discussion topics. Moreover, the data was interpreted by reference and expertise team. Data was analysed by SWOT analysis method (Strength, Weakness, Opportunity and Threat). The results of internal environmental analysis (ALI), strength variable value was greater than weakness variable value (379> 355). Results of analysis of the external environment (ALE), the chance variable values is smaller than threat variable value (360 <390). Patterns of innovation assistance accomodated SL-PTT on aspects bases on paddy power (potential region, motivation, market access); aspects of weakness bases (Adoption of technology, labor, cost of production); aspects of opportunity bases (Agroecosystems, VUB rice, promotion of innovation SL-PTT); and aspects of threats bases (climate, mentoring systems, technology development). Keywords: Accompaniment patterns, FS-ICM rice